THE NEED AND AVAILABILITY ANALYSIS OF THE NEED AND AVAILABILITY OF GREEN OPEN SPACE IN THE UNIFA MAKASSAR CAMPUS ENVIRONMENT - noviar nurdin kasim (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
This study aims to analyze the level of need and availability of Green Open Space in the Fajar Makassar University Campus. This research is descriptive quantitative. Data was collected through observation, interviews and literature study. The data were analyzed by analyzing the demand for oxygen and carbon dioxide produced, to get the amount of green open space and the number of trees needed. The results of this study indicate that the Fajar Makassar University campus requires additional green open space area of ​​4,718.5 m² which contains 16.41 fruit trees.